Thyroid Dysfunction Across Stages Of Chronic Kidney Disease: A Cross-Sectional Study At A Tertiary Care Hospital. - Avinash S, Avinash S; Rao Tati, Srinivasara (Journal of Neonatal Surgery, 2025)
Background: Thyroid dysfunction is common in chronic kidney disease (CKD) and could have a bi-directional relationship with renal disease. There is subclinical hypothyroidism, overt hypothyroidism and low-T3 syndrome, all with different clinical and prognostic implications. There are scarce prevalence data available from tertiary care in India that are presented in a systematic manner on the basis of staging. Materials and Methods: The study was a cross-sectional design that involved 200 adult CKD patients (KDIGO CKD staging) and 100 age and sex matched euthyroid control patients. Free T3, free T4, TSH and anti-TPO antibodies were measured. Amiodarone, lithium, glucocorticoids and primary thyroid disease patients were excluded. Results: There were 77 (38.5%) CKD patients with thyroid dysfunction, compared to 8 (8.0%) controls (p<0.001). The largest group of patients had subclinical hypothyroidism (22.0%), followed by low-T3 syndrome (7.5%) and overt hypothyroidism (9.0%). The prevalence rate went up from 18.2% (CKD 3) to 56.4% (CKD 5/dialysis). There was a strong inverse correlation between FT3 and serum creatinine (r=−0.42, p<0.001). eGFR <30, diabetes (aOR 1.8), and proteinuria (aOR 1.7) were independent predictors of thyroid dysfunction. Conclusion: Thyroid dysfunction is common in CKD and increases with disease progression. CKD Stage 4–5 patients warrant routine thyroid screening. The low-T3 syndrome, while not requiring levothyroxine, serves as a prognostic marker of advanced disease..